Georges Vanier - Bertrand, Luc (Célébrités canadiennes, 1993)
Les diverses étapes de la prestigieuse carrière de cet ancien gouverneur général du Canada.

Hormidas [Hormisdas] Laporte (1850-1934). Une petite maison, un grand homme - Cloutier, Gabrielle (Cahiers d'histoire du Sault-au-Récollet, 1993)
Keywords: Alimentation; Assurance; Commerce de détail; Laporte (famille); Magasins; Maires; Épicerie

Le chevalier oublié - de Lagrave, Jean-Paul (Cap-aux-Diamants, 1993)
Keywords: Chomedey de Maisonneuve, Paul de (Maisonneuve, Paul de Chomedey de)

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

La Nouvelle-France sous Joseph-Antoine Le Febvre de La Barre, 1682-1685: lettres, mémoires, instructions et ordonnances - Dubé, Pauline (Septentrion, 1993)
Keywords: Autochtones; Français; Gouverneurs

Entrevue avec Phyllis Lambert - Gagnon-Pratte, France (Continuité, 1993)
Keywords: Centre canadien d'architecture; Lambert, Phyllis

L'apport des coalitions de quartier dans l'élargissement de la démocratie locale - Lambert, Claudette (Université du Québec à Montréal, 1993)
Keywords: Groupes populaires

La place de Médéric Lanctôt dans l'évolution du nationalisme québécois - Lefebvre, Luc (Université de Montréal, 1993)
Keywords: Lanctôt, Médéric; Nationalisme

Les limites de la démocratie, les frontières de l'autonomie - Lustiger-Thaler, Henri (Recherches sociographiques, 1993)
Keywords: Groupes populaires; Hôtel de ville; Maires; Rassemblement des citoyens et citoyennes de Montréal

La ville: un milieu d'engagement politique privilégié pour les femmes: le cas de Montréal - Maillé, Chantal (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Histoire des maires de Montréal - Marsolais, Claude-V.; Desrochers, Luc; Comeau, Robert (Études québécoises, 1993)
Keywords: Maires

Les Québécoises et le mouvement pacifiste (1939-1967) - Monet-Chartrand, Simonne (Écosociété, 1993)
Keywords: Femmes; Guerre

Les maires de Saint-Laurent et les conseils municipaux: une histoire à découvrir - Nadon, Mario (Ville de Saint-Laurent et Groupe Litho-Graphic, 1993)
Keywords: Conseillers municipaux; Maires; Saint-Laurent (ville)

Les femmes et la prise de décision au niveau municipal - Pelletier, Lyse (Les Bâtisseuses de la Cité, 1993)
Keywords: Conseillers municipaux; Femmes

Les femmes et le vote au Bas-Canada, 1791-1849 - Picard, Nathalie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Élections

Marguerite Lacorne, conseillère de Jacques Viger - Robillard, Denise (Les Bâtisseuses de la Cité, 1993)
Keywords: Lacorne (famille); Maires; Viger, Jacques